2012
DOI: 10.1186/1476-7120-10-24
|View full text |Cite
|
Sign up to set email alerts
|

Can echocardiographic particle image velocimetry correctly detect motion patterns as they occur in blood inside heart chambers? A validation study using moving phantoms

Abstract: AimsTo validate Echo Particle Image Velocimetry (PIV)MethodsHigh fidelity string and rotating phantoms moving with different speed patterns were imaged with different high-end ultrasound systems at varying insonation angles and frame rates. Images were analyzed for velocity and direction and for complex motion patterns of blood flow with dedicated software. Post-processing was done with MATLAB-based tools (Dflow, JUV, University Leuven).ResultsVelocity estimation was accurate up to a velocity of 42 cm/s (r = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 18 publications
(20 reference statements)
0
33
0
Order By: Relevance
“…Echocardiographic particle image velocimetry (E‐PIV) is based on microbubble contrast‐enhanced ultrasound. E‐PIV can display and quantify the velocity and direction of flow by tracing microbubbles, allowing new insights into flow patterns to be discovered, such as vortices . Dilated cardiomyopathy (DCM) is a form of primary cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Echocardiographic particle image velocimetry (E‐PIV) is based on microbubble contrast‐enhanced ultrasound. E‐PIV can display and quantify the velocity and direction of flow by tracing microbubbles, allowing new insights into flow patterns to be discovered, such as vortices . Dilated cardiomyopathy (DCM) is a form of primary cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…E-PIV can display and quantify the velocity and direction of flow by tracing microbubbles, allowing new insights into flow patterns to be discovered, such as vortices. 10,[12][13][14] Dilated cardiomyopathy (DCM) is a form of primary cardiomyopathy. There is much research about its pathogenesis, clinical manifestations, and therapies from the aspect of its histopathology, functional morphology, and myocardial mechanics.…”
mentioning
confidence: 99%
“…The highest similarity of the patterns between subsequent frames enables to calculate displacement and velocity of blood flow. We and others already have demonstrated that the concept of PIV echocardiography is feasible to analyze changes in position of small particles that drift with blood . Furthermore, PIV echocardiography can be used to obtain information about the energy dissipation in the flow field …”
mentioning
confidence: 99%
“…In brief, previously validated experimental software named “Hyper Flow” (v.8, AMID, Sulmona, Italy) was used, which is not vendor‐specific. Echo‐PIV quantification method is characterized by a substantial cutoff for the estimation of the high velocities because of the insufficient frame rate of the echocardiographic acquisition, although it was demonstrated that the direction of the flow remains estimated with good accuracy . The cutoff limitation affects the flow field only during peak velocity and close to the valve while the intra‐cavity circulation, that is associated with lower velocities, is not influenced.…”
Section: Methodsmentioning
confidence: 99%
“…Echo-PIV quantification method is characterized by a substantial cutoff for the estimation of the high velocities because of the insufficient frame rate of the echocardiographic acquisition, although it was demonstrated that the direction of the flow remains estimated with good accuracy. 22 The cutoff limitation affects the flow field only during peak velocity and close to the valve while the intra-cavity circulation, that is associated with lower velocities, is not influenced. However, to ensure that acquisition settings are not affecting the results, all the subsequent quantifications were expressed in dimensionless terms.…”
Section: Echo-piv: Image Analysismentioning
confidence: 99%